A New Metamorphic Parallel Leg Mechanism with Reconfigurable Moving Platform. (14th March 2020) - Xu, Yong; Liang, Zheng; Liu, Jiali
Abstract : This paper proposes the concept of full configuration state of metamorphic mechanism. Based on the concept, the configuration synthesis principle of metamorphic parallel mechanism is put forward. Firstly, a metamorphic parallel mechanism in full configuration state is synthesized, and then full configuration state evolves into a specific configuration state by increasing constraints or decreasing degrees of freedom. A reconfigurable moving platform based on the triple symmetric Bricard spatial closed-loop mechanism with a single degree of freedom is proposed. Based on this, a new method for switching motion configuration states of the metamorphic parallel mechanism is constructed. According to the configuration synthesis principle presented above, a novel metamorphic parallel mechanism that can switch between three- and four-degree-of-freedom is synthesized, and then the triple symmetric Bricard spatial closed-loop mechanism is used as the reconfigurable moving platform (that is, the reconfigurable foot of a walking robot) of the metamorphic mechanism, and thus, a novel metamorphic parallel leg mechanism is created. The screw theory is used to verify the degrees of freedom of the new type of metamorphic parallel leg. The proposed metamorphic parallel leg mechanism is expected to improve flexibility and adaptability of walking robots in unstructured environment.